2011
DOI: 10.1111/j.1365-2133.2011.10212.x
|View full text |Cite
|
Sign up to set email alerts
|

Filaggrin polymorphism P478S, IgE level, and atopic phenotypes

Abstract: Our results suggest that the FLG P478S polymorphism may confer susceptibility to the development of AD among Chinese individuals and may be modified by IgE levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 34 publications
2
35
0
Order By: Relevance
“…Similarly, Wang et al . showed that the association between FLG variants and eczema was limited to a subset of children with IgE levels ≥ 100 kU/L . Hence, we suggest considering the combined effect of both risk factors rather than taking the cause–effect approach could lead to a better risk assessment.…”
Section: Discussionmentioning
confidence: 91%
“…Similarly, Wang et al . showed that the association between FLG variants and eczema was limited to a subset of children with IgE levels ≥ 100 kU/L . Hence, we suggest considering the combined effect of both risk factors rather than taking the cause–effect approach could lead to a better risk assessment.…”
Section: Discussionmentioning
confidence: 91%
“…Sequences specifically present or absent in the A or Aʹ variant might affect filaggrin processing and be a hidden factor for AD development – a hypothesis to be tested in other epidemiological or experimental settings. In this sense, there was an interesting report from Taiwan showing that the FLG polymorphism P478S (rs11584340) might confer susceptibility to AD – the GG genotype increased the risk of AD. P478S polymorphism originates from the G>A SNP located 1432 bp from the open reading frame (Fig.…”
Section: Copy‐number Variation and Associated Genotypes Of Flg In Kormentioning
confidence: 99%
“…These mutations were present in 31.4 % of 261 patients with AD but were not associated with asthma [ 35 ]. Also Li et al [ 32 ] and Wang et al [ 34 ] studied FLG mutations in the Chinese population but, in contrast to the study by Zhang et al, found a positive association with asthma. Particularly the study by Wang et al found that the P478S GG genotype signifi cantly increased the risk of developing asthma in patients with AD, OR = 4.68 (1.37-16.03).…”
Section: Populations Of Non-european Descentmentioning
confidence: 94%